Prognostic value of tissue and circulating levels of IMP3 in prostate cancer. Issue 7 (4th March 2014) - Szarvas, Tibor; Tschirdewahn, Stephan; Niedworok, Christian; Kramer, Gero; Sevcenco, Sabina; Reis, Henning; Shariat, Shahrokh F.; Rübben, Herbert; vom Dorp, Frank
Abstract : Tissue levels of the oncofetal protein insulin‐like growth factor 2 (IGF2) messenger RNA‐binding protein 3 (IMP3) have been associated with poor prognosis in multiple human malignancies. However, its circulating levels have not yet been analyzed. Therefore, the aim of this study was to assess the prognostic value of both serum and tissue levels of IMP3 in prostate cancer (PC). IMP3 protein expression was analyzed in 124 PC and 13 benign prostate hyperplasia (BPH) patients using immunohistochemistry. Gene expression levels of IMP3 and its molecular target IGF2 were analyzed in 29 frozen and 26 paraffin‐embedded PC tissues using real‐time polymerase chain reaction and immunohistochemistry. Serum IMP3 levels were assessed in 94 PC and 20 BPH patients as well as in 20 controls using enzyme‐linked immunosorbent assay. IMP3 immunostaining was present in 0% (0/13) of BPHs, 15% (15/101) of clinically localized PCs and 65% (15/23) of palliatively treated metastatic PCs ( p < 0.001). Accordingly, serum IMP3 concentrations were significantly higher in PC compared to BPH patients which were higher than those in controls ( p < 0.001 each). The highest concentrations were detected in metastatic PC patients ( p = 0.036). In patients who underwent radical prostatectomy high IMP3 serum levels were independently associated with poor cancer‐specific survival. IMP3 gene and protein expressions were not correlated with those of IGF2. In conclusion, we found enhanced IMP3 levels in tissue and serum samples of PC patients compared to non‐PC men. Moreover, IMP3 was associated with metastasis and PC‐specific survival. The tumor promoting effect of IMP3 appears to be independent from its regulatory role on IGF2 in PC. Abstract : What's new? For an asymptomatic tumor like prostate cancer, saving lives depends on early diagnosis. But PSA testing identifies many cancers that might never become harmful, leading to expensive, unnecessary treatments. Thus, the search is on for a test to identify only those cancers likely to cause harm. This study examined serum levels of a cancer marker, IMP3, and found that patients with prostate cancer had higher levels of circulating IMP3 than those with benign prostate hyperplasia. Higher levels correlated with poorer survival, and those whose cancers metastasized had the highest amounts, suggesting this marker might help identify the most dangerous cancers.